Judicial Pardon in Update of the Criminal System Against Middle Crimes - Sagung Putri M.E. Purwani; Putu Mery Lusyana Dewi (Yustisia Jurnal Hukum, 2021)
Judicial pardon is a concept of punishment in which a defendant is proven guilty but is not sentenced by judges. It is not explicitly regulated in the Criminal Code in Indonesia. Therefore, it is important to examine the concept, specifically in the event of the renewal of criminal law toward minor offenses. This research aimed to determine the concept of judicial pardon in reforming the criminal system for minor offenses and its ideal setting in the future. This normative legal research was conducted with a  statutory,  a  concept,  a  comparative,  and  a  case  approach. The results indicated that the concept of judicial pardon in the renewal of the criminal system could be an alternative judges’ decision on minor offenses. Philosophically, it is under the values of the 1945 Constitution of Indonesia, and sociologically, it is a response to many public criticisms of law enforcement against a minor criminal offense that is considered unfair. Juridically, the rationale or basis for this concept can be found in the Law on Judicial Power, where judges are obliged to dig, follow, and understand the legal values and the sense of justice in society. The ideal judicial pardon arrangement in Indonesian criminal law should be considered with several provisions regarding crime severity limitation and further provisions after being granted a pardon.